The Rhetoric of Barbarism: Representations of Northern Barbarians and the Image of Emperors in Pagan Authors of the Early Theodosian Period - Stone, Robert G (2021)
During the fourth century, the Roman Empire underwent major shifts in its cultural complexion. Alongside the growing influence of Christianity, there were also rapid changes in the roles and positions of northern barbarians. No longer primarily fighting against the empire, they were also an increasingly significant presence in the empire’s armies, providing troops and even leading them. For some non-Romans, it was possible even to rise to positions such as the consulship. The potential for high status available to these peoples and their increased prominence in the imperial courts in turn reduced the opportunities open to the traditional pagan elite and invited questions from them and their supporters over whether these changes were positive for the empire and who could be considered truly Roman and who was a barbarian. Pagan authors writing during the early Theodosian dynasty initially appear to have answered this in accordance with the literary tradition and contemporary visual representations; the emperor and his soldiers were Roman and embodied virtues like disciplina and virtus while those they fought were savage, greedy barbarians. However, the traditional rhetoric used to describe the barbaric non-Roman could also be developed further to encourage a deeper comparison between the two sides. Authors were prepared to create more nuanced portrayals of non-Romans, both internal and external. For panegyrists like Themistius this depth of character served as a means of showing support for imperial policies such as Theodosius’ policy of Gothic integration and service in the army. On the other hand, authors such as Ammianus, Eunapius and the anonymous author of the Historia Augusta juxtaposed positive and negative representations of barbarians with Romans in order to evaluate whether those living within the empire were maintaining the behaviour and standards expected of Roman citizens, in particular the emperors who were responsible for the defence of the empire and who publicly portrayed themselves as model Romans. For these authors, their depictions of barbarians served as a malleable rhetorical device to assess the performance of the emperor and by extension the health of the empire itself at a time when the influence of the traditional pagan elite was under challenge.